Pre-genetic Diagnosis and Pre-natal Diagnosis: Legal and Ethical Discussion - Игновска, Елена (Меѓународен Славјански Универзитет „Гаврило Романович Державин“, Меѓународен Центар за Славјанска Просвета - Свети Николе, 2019)
Medical science allows to address each individual from his/hers particular genetic makeup on an embryonic level, either in vivo (prenatal diagnosis, hereinafter PND) or in vitro (preimplantation genetic diagnosis, hereinafter PGD), a sort of personalized medicine. Both technologies assist reproduction in order to identify and possibly address genetic alterations. Therefore, they have been subjected to ethical and legal controversies, mostly regarding to issues such as: the dignity of the embryos to be discarded, the voice of the unheard – the future child-, the renaissance of eugenics policies- and, the lack of a universal normative framework that circumscribes it. The European Court of Human Rights has already ruled that access to such genetic testing is a human right protected under the European Convention of Human Rights –inter alia, in re Costa and Pavan v. Italy. This right is argued and affirmed in many international documents and becomes a European consensus among the Member States of the Council of Europe. Thus, the discussion in this article will go beyond its affirmation, into the sphere of relating the right to its counterpart –the obligation to create healthy offspring, i.e. reproductive responsibility in the Republic of Macedonia and internationally.
Keywords: PGD, PND, law and ethics.